2020
DOI: 10.1086/705550
|View full text |Cite
|
Sign up to set email alerts
|

Subsidy Design in Privately Provided Social Insurance: Lessons from Medicare Part D

Abstract: Timmins, and numerous seminar participants. Decarolis is grateful to the Sloan Foundation (grant 2011-5-23 ECON) for financial support. We also gratefully acknowledge support from the National Science Foundation (SES-1357705) and the National Institute on Aging (5P01AG005842-29). The views expressed herein are those of the authors and do not necessarily reflect the views of the National Bureau of Economic Research. NBER working papers are circulated for discussion and comment purposes. They have not been peerr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 39 publications
3
28
0
Order By: Relevance
“…We do not explore the effect of the subsidy on entry and exit. While insurers and plans in our data do enter and exit, the median share captured by new entrants is 0.18% Decarolis et al (2015). make a similar argument.…”
supporting
confidence: 61%
See 2 more Smart Citations
“…We do not explore the effect of the subsidy on entry and exit. While insurers and plans in our data do enter and exit, the median share captured by new entrants is 0.18% Decarolis et al (2015). make a similar argument.…”
supporting
confidence: 61%
“…As our counterfactual benchmarks are within the support of the current benchmark distribution, the role (or lack thereof) of past entry and exit on consumer surplus should be informative about its impact on consumer surplus in the counterfactuals. Decarolis et al (2015) use a similar logic in their analysis of Medicare Part D. Maruyama (2011) studies entry and pricing in Medicare+Choice but does not endogenize product characteristics.…”
Section: An Equilibrium Approximation Approach To Counterfactual Analmentioning
confidence: 99%
See 1 more Smart Citation
“…A full equilibrium approach to simulating counterfactual equilibria would allow for dynamic interactions between consumers’ plan choices and insurers’ decisions regarding entry and exit and plan design . Others have modeled how Part D insurers may alter premiums but not other plan attributes in response to prospective changes in the subsidy structure (Decarolis et al., ), switching costs (Polyakova, ), inertia (Fleitas, ), and consumer inattention (Ho et al., 2015) . None have modeled changes to choice architecture in Part D per se.…”
Section: Caveats and Opportunities For Future Researchmentioning
confidence: 99%
“…Conversely, policies that increase insurers’ revenues are likely to be eroded due to the competitive design of the CMS bidding process or otherwise targeted by regulators. In fact, prior work found that plan premiums are set near their marginal costs (Decarolis et al., ).…”
Section: Caveats and Opportunities For Future Researchmentioning
confidence: 99%